A study on bone cement containing magnesium potassium phosphate for bone repair. Issue 1 (1st January 2018) - Zhang, Zhixiang; Yang, Zaijun; Chen, Zhenyong; Kang, Tairan; Ding, Xiang; Li, Yunxiang; Liao, Yongmei; Chen, Chunhui; Yuan, Huipin; Peng, Hongwei
Abstract: A novel type of bone cement, magnesium potassium phosphate cement (MKPC), was fabricated by mixing 5% phosphoric acid with magnesia, potassium dihydrogen phosphate, sucrose, hydroxyapatite, and sodium tri-polyphosphate powders. The surface morphology and mechanical strength of MKPC were investigated together with tissue responses following implantation into rabbit condylar defects, using commercially available calcium phosphate cement (CPC) as the control. The results showed that MKPC had a higher compressive strength (25.40 ± 0.61 MPa) than CPC (16.45 ± 1.91 Mpa) and did not initiate foreign body reaction, inflammation, or necrosis in vivo . Both cements were resorbed by creeping substitution, in which the resorbed cement was replaced by the newly formed bone. MKPC had a higher resorption rate and enhanced bone regeneration compared to CPC. The data presented here indicate that MKPC could be a potential bone void filler for bio-adhesion in clinical applications.